2009
DOI: 10.1160/th09-04-0215
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 96-well plate aggregometry and measurement of thrombi adhesion to determine aspirin and clopidogrel effectiveness

Abstract: Aspirin and clopidogrel are key anti-thrombotic therapies. Results from platelet reactivity testing during therapy, have been shown to correlate with future events and would allow for the optimisation of therapy. However, there is little agreement among current tests and there remains a clear clinical need for a universal standardised test. It was the objective of this study to explore the potential of 96-well plate aggregometry as a definitive clinical test of platelet reactivity with respect to aspirin and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 43 publications
7
41
0
Order By: Relevance
“…As we have previously reported in standard 96-well plate and optimul kinetic aggregometry [1,[4][5][6], we found that aspirin significantly inhibited ( p < 0.05) aggregation induced by EPI and completely abolished responses to AA and collagen. PAM, however, significantly attenuated ( p < 0.05) aggregation induced by all agonists tested, except for ristocetin, which acts through a process that involves agglutination and not aggregation.…”
supporting
confidence: 85%
“…As we have previously reported in standard 96-well plate and optimul kinetic aggregometry [1,[4][5][6], we found that aspirin significantly inhibited ( p < 0.05) aggregation induced by EPI and completely abolished responses to AA and collagen. PAM, however, significantly attenuated ( p < 0.05) aggregation induced by all agonists tested, except for ristocetin, which acts through a process that involves agglutination and not aggregation.…”
supporting
confidence: 85%
“…A further variation between research groups is the duration of shaking, reports include bursts of intermittent shaking for up to 18 minutes or one continuous shake for 5 minutes (17,25). We have previously published traces of absorbance measured every 15 seconds following shaking after agonist stimulation over 16 minutes (12). Since this is slower than LTA, we have subsequently utilized a stand-alone high-speed shaker that provides uniform mixing through the production of vortices in each well of the plate and generates more rapid platelet responses.…”
Section: -Well Plate Aggregationmentioning
confidence: 99%
“…Optimization and characterization of the Optimul assay have been previously reported. 13,14,17 An Optimul panel was defined as abnormal if the dose-response curve was below the lower limit of the 95% reference interval for .1 agonist.…”
Section: Assessment Of Platelet Functionmentioning
confidence: 99%